2022
DOI: 10.1021/acsnano.2c05812
|View full text |Cite
|
Sign up to set email alerts
|

Melimine-Modified 3D-Printed Polycaprolactone Scaffolds for the Prevention of Biofilm-Related Biomaterial Infections

Abstract: Biomaterial-associated infections are one of the major causes of implant failure. These infections result from persistent bacteria that have adhered to the biomaterial surface before, during, or after surgery and have formed a biofilm on the implant's surface. It is estimated that 4 to 10% of implant surfaces are contaminated with bacteria; however, the infection rate can be as high as 30% in intensive care units in developed countries and as high as 45% in developing countries. To date, there is no clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…[65] A limitation of the XPS method is the lack of molecular specificity. [78] 2.4. X-ray absorption fine structure (XAFS)…”
Section: Methodological Features Of Xpsmentioning
confidence: 99%
See 1 more Smart Citation
“…[65] A limitation of the XPS method is the lack of molecular specificity. [78] 2.4. X-ray absorption fine structure (XAFS)…”
Section: Methodological Features Of Xpsmentioning
confidence: 99%
“…The quantitative measurements are affected by the peak intensity, accuracy of the relative sensitivity factor, surface volume homogeneity, signal‐to‐noise ratio, correction for the energy dependence of electron mean free path, correction for the electron transmission function, and degree of the sample degradation [65] . A limitation of the XPS method is the lack of molecular specificity [78] …”
Section: X‐ray Techniques For Materials Characterizationmentioning
confidence: 99%
“…[1][2][3] According to current estimates, about 4-10% of implant surfaces are contaminated with bacteria from various sources, while the infection rate in intensive care units is estimated to be as high as 30-45%. [4,5] The alarming statistics emphasize the importance of developing strategies to render the DOI: 10.1002/mabi.202300296 implant surfaces free of infection to improve patient outcomes. [6,7] Further, the increasing prevalence of antimicrobial resistance has greatly diminished the effectiveness of antibiotic-based treatment protocols for infections caused by multidrug-resistant and extensively resistant strains.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cometta et al functionalized the surface of 3D-printed poly(𝜖-caprolactone) (PCL) with an antimicrobial peptide, melimine, and demonstrated its ability to substantially decrease bacterial viability and biofilm formation. [5] Similarly, Lin et al demonstrated PCL encapsulated with HHC36, a synthetic antimicrobial peptide, as a coating option to mitigate catheter-associated urinary tract infections. [20] Among several natural antimicrobial substances, lysozyme is known to be the first line of defense that imparts innate immunity to the host against a wide spectrum of pathogens with high efficacy and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation